Effect of the urease-derived peptide Jaburetox on the central nervous system of Triatoma infestans (Insecta: Heteroptera) - Galvani, Gerónimo Luis (2015)
Triatoma infestans is the main vector of Chagas'disease in Southern Cone countries. In triatomines, symptoms suggesting neurotoxicity were observed after treatment with Jaburetox (Jbtx), the entomotoxic peptide obtained from jackbean urease. Here, we study its effect in the central nervous system (CNS) of this species.